Penerapan Metode Ceramah Plus dalam Mata Pelajaran Pendidikan Agama Islam Pada Peserta Didik SMP NU Kajen - Mardiah; Prayogi, Arditya (Lembaga Einstein College (LEC), 2024)
In general, there are still PAI teachers who only use the lecture method (conventionally) in their learning. This causes students to feel bored quickly during the learning process. However, this conventional lecture method can be varied with other methods to become a plus lecture method. The lecture plus method is a teaching method that uses more than one method, namely the lecture method combined with other methods. The purpose of implementing the plus lecture method is to fix various specific weaknesses of using the conventional lecture method. Thus, this article aims to provide an overview of the application of the plus lecture method at NU Kajen Middle School as well as the supporting and inhibiting factors in its application. The article is field research with a qualitative descriptive approach. Data collection techniques are carried out using interviews, observation and documentation. Technical data analysis is carried out by reducing data, presenting data, drawing conclusions. From the results of the study, it is clear that in general the plus lecture method at NU Kajen Middle School is carried out in three stages, the first is delivering the material, the second and third stages are adjusting the plus lecture method that you want to use. The lecture plus method that is often used is the Lecture Plus Question and Answer and Assignment method. In its application, the lecture plus method has supporting factors, including having sufficient references, having adequate infrastructure, good teaching techniques, religion-based schools and teacher professionalism. Meanwhile, inhibiting factors include lack of material preparation, students experiencing learning boredom, lack of availability of textbooks